"Cómaros verdes". The First Galician Post-war Poetry Book - Arias Chachero, Patricia (Madrygal. Revista de Estudios Gallegos, 2015)
In 1947, Cómaros verdes by Iglesia Alvariño is published, it is considered the first important post-war Galician collection of poems. In the present article we will try to analyze the circumstances surrounding the appearance of the aforesaid mentioned book.